Análisis y diseño de la distribución física de una empresa textil - Cano Menéndez, Yander Daniel (2010)
Currently the market for domestic textile fmns have been affected due to political factors in the national economy and increasing demand for its products, which has forced them to acquire machinery indiscriminately, adapting or splitting areas, reducing corridors etc .., in consequence comes the need to expand its facilities due to space limitations. It is here where they see the need to make a plant design that allows them to optimize their resources such as machinery, human resources, materials and auxiliary services, maximizing the production levels of the company, reduce the waste of time result of unnecessary movements, effectively use all available space, ensure the safety and health of workers.